Biologic treatment for psoriasis in cancer patients: should they still be considered forbidden?. (4th July 2022) - Mastorino, Luca; Dapavo, Paolo; Avallone, Gianluca; Merli, Martina; Cariti, Caterina; Rubatto, Marco; Pala, Valentina; Quaglino, Pietro; Ribero, Simone
Abstract: Available evidence to guide clinicians in the management of psoriasis patients with a history of malignancies is scarce. The latest generation of biological drugs is traditionally considered to be safe in patients with previous malignancy, although only case reports and short case series on the use of biological drugs in this population are available in the literature. In this paper, we present the experience of our clinic on 37 psoriatic patients with a previous diagnosis of neoplasia treated subsequently with biological drugs. Subsequently, a systematic review of the literature was performed and 38 cases were found. The main biologic used in our patients and the patients described in the literature was secukinumab. In both populations treatment with biologics was safe, disease progressions reported were not related to treatment. Based on our experience, which is the largest currently available, and the cases reported in the literature the treatment of psoriasis in patients with previously diagnosed cancer with biologics against TNFalpha, IL17, IL23, and IL12 would appear to be safe. The first experience on the use of Risankizumab and brodalumab on this special population is also reported in our series.